A new species of Characidium Reinhardt, 1867 (Characiformes: Crenuchidae) endemic to the Atlantic Forest in Paraná State, southern Brazil - Melo,Marcelo R. S. (2016)
ABSTRACT A new species of Characidium is described based on specimens obtained from the highland streams of the Serra do Mar, Atlantic Forest Biome, in Paraná State, Southern Brazil. The new species is possibly a member member of the C. lauroi group, which is diagnosed by having the isthmus unscaled, bars poorly marked, and spots on sides of body, and is composed by four additional species: C. japuhybense ; C. lauroi ; C. oiticicai ; and C. schubarti . The new species differs from its congeners with naked isthmus, except C. helmeri , by having 15-18 principal caudal-fin rays; and 10-12 pectoral-fin rays; and from C. helmeri , by having a slender body, tip of pectoral fin not reaching origin of pelvic fin, tip of pelvic fin not reaching beyond anus, supraorbital present and well developed, and by lacking vertically elongated dashes on sides of body. The new species is known from tributaries of the rio Jordão, in the rio Iguaçu Basin, and rio Taquari, a tributary of the rio Ribeira de Iguape coastal drainage.